A new cicada (Hemiptera: Cicadidae) species from Brazil with a detailed description of the genus Parnisa Stål, 1862 and key to the known species - Sanborn, Allen F.; Gonzaga, Luiz P.; Takiya, Daniela M. (Zootaxa, 2024)
The new cicada species Parnisa infuscata sp. nov. is described, along with its calling song, from Minas Gerais State in Brazil. The genus Parnisa Stål, 1862 is redescribed to provide additional details on its morphology since the abbreviated original generic description was based only on a few wing characters. A key for the 14 known species of the genus is provided.